Scope and relevance of a pulmonary biopharmaceutical classification system AAPS/FDA/USP Workshop March 16-17th, 2015 in Baltimore, MD - Jayne E. Hastedt; Per Bäckman; Andrew R. Clark; William Doub; Anthony Hickey; Guenther Hochhaus; Phil J. Kuehl; Claus-Michael Lehr; Peter Mauser; Jason McConville; Ralph Niven; Masahiro Sakagimi; et al. (SpringerOpen, 2016)
Abstract The Biopharmaceutics Classification System (BCS), developed in the 1990s for oral immediate release drugs, is utilized by R&D scientists and regulators to streamline product development and regulatory approval timelines. This elegant, science-based approach is based on three in vitro parameters representing a combination of drug substance physicochemical and physiological properties with respect to oral administration; specifically a dose number, dissolution number, and absorption number. Interest in applying similar principles to pulmonary drug products is increasing. To date the focus has been on dissolution of drugs in the lung. A workshop co-sponsored by the AAPS, FDA, and USP was held in March 2015 in Baltimore to evaluate if a systematic framework to classify pulmonary drugs could be established, and the scope and relevance of such a classification scheme. The focus of the workshop was to address factors influencing drug delivery and action in the lungs rather than the development of a specific model or system. Presentations included: the history and evolution of the oral BCS (described as the "giBCS" by Gordon Amidon), lung physiology and the fate of inhaled drugs, regional aerosol deposition and dose, macroscopic clearance mechanisms, particle dissolution, drug permeability, absorption and their interplay with pharmacokinetics and pharmacodynamics. Background discussions were followed by three separate breakout sessions each focused on the BCS concepts of dose, dissolution, and absorption numbers as they would apply to pulmonary drug delivery. The workshop concluded that a classification system, if fully developed, would be a useful tool for formulators and discovery chemists. The scope of such a system, at this point in time, would not include aspects relevant to regulatory relief. The goals of the workshop were met by identifying an opportunity to develop a model to classify pulmonary drugs based on physicochemical attributes specific to lung physiology and drug delivery.